Patient perceptions of glucocorticoid side effects: a cross-sectional survey of users in an online health community. Issue 4 (3rd April 2017) - Costello, Ruth; Patel, Rikesh; Humphreys, Jennifer; McBeth, John; Dixon, William G
Abstract : Objectives: To identify the side effects most important to glucocorticoid (GC) users through a survey of a UK online health community (Healthunlocked.com). Design: Online cross-sectional survey. Setting: Participants were recruited through Healthunlocked.com, an online social network for health. Participants: Adults who were currently taking GCs, or had taken GCs in the past month. Method: Responders scored the importance of listed side effects from 1 to 10, with 10 being of high importance to them. For each side effect, histograms were plotted, and the median rating and IQR were determined. Side effects were ranked by median ranking (largest to smallest) and then IQR (smallest to largest). The scores were categorised as low (scores 1–3), medium (scores 4–7) and high (scores 8–10) importance. Results: 604 responders completed the survey. Histograms of side effect scores showed a skew towards high importance for weight gain, a U-shaped distribution for cardiovascular disease (CVD), diabetes, eye disease and infections, and a skew towards low importance for acne. When ranked, the side effect of most importance to responders was weight gain (median score=9, IQR 6–10) followed by insomnia and moon face with equal median score (8) and IQR (5–10). Three serious side effects, CVD, diabetes and infections, were ranked of lower importance overall but had wide ranging scores (median score=8, IQR 1–10). Conclusions: The three most highly rated side effects were not clinically serious but remained important to patients, perhaps reflecting their impact on quality of life and high prevalence. This should be taken into consideration when discussing treatment options and planning future GC safety studies.